2022
DOI: 10.3390/sports10090129
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Trainers’ Educational Qualification and Experience and Its Association with Their Trainees’ Musculoskeletal Pain: A Cross-Sectional Study

Abstract: This is a cross-sectional study that examined the association between fitness trainers’ educational qualifications and experience, and the risk of their trainees’ musculoskeletal pain. The study included 1177 trainees (aged 15–60 years) from 74 fitness centers in Bangladesh. Data were collected by using the Nordic musculoskeletal questionnaire, including potential confounders such as demographic factors (e.g., age, occupation), and training-related factors (e.g., workout knowledge, overweight lifting). Multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…The most common site of injury was the back (17.2%), followed by the shoulder (11.0%) and the knee (7.6%). Similar to our result, a study conducted by Ahmed et al reported that the back was the most commonly affected site for gym injuries, followed by the shoulder and knee [ 22 ]. In contrast to our study, Shinde and Sahasrabuddhe reported the shoulder as the most commonly affected site for gym injuries, followed by the lower back and knee [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…The most common site of injury was the back (17.2%), followed by the shoulder (11.0%) and the knee (7.6%). Similar to our result, a study conducted by Ahmed et al reported that the back was the most commonly affected site for gym injuries, followed by the shoulder and knee [ 22 ]. In contrast to our study, Shinde and Sahasrabuddhe reported the shoulder as the most commonly affected site for gym injuries, followed by the lower back and knee [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…Waryasz et al (2016) reported that PTs play an important role in preventing injuries through professionalism [ 50 ]. Ahmed et al (2022) found that the involvement of a PT with considerable expertise and experience is instrumental to preventing bone and joint injuries [ 51 ], Which is also supported by the findings of this study.…”
Section: Discussionsupporting
confidence: 87%
“…Osiński [3] expressed the opinion that an instructor should present a high level of technical training and physical fitness in order to clearly convey his own knowledge and skills. In turn, Ahmed et al [28] expressed concern that despite the growing popularity of services such as personal training or group fitness classes, as well as the increasing number of people with trainer's licenses, the profession is still not fully regulated. The authors found that instructors enjoy a steadily growing authority, despite doubts about their competence.…”
Section: Discussionmentioning
confidence: 99%